The Implementation of Game-based Learning Using Kahoot Application in Teaching Vocabulary at the Tenth-grade Students of SMKN 1 BONE - Perakawardani, Lastry; Taslim, Taslim; Muhdar, Fahriadi (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aimed to determine whether the implementation of game-based learning using the 'Kahoot!' application significantly impacts the English vocabulary acquisition of students at SMKN 1 Bone. The research employed a pre-experimental method with a one-group pre-test and post-test design, focusing on assessing whether there is an improvement in students' vocabulary after applying game-based learning with the 'Kahoot!' application. The instrument used was a vocabulary test administered as both a pre-test and post-test. The study's findings indicate an improvement among the tenth-grade students, as evidenced by the average pre-test score of 48.5, which increased to 86.8 in the post-test—that is, it increased by 38.3%. Observations also confirmed that implementing game-based learning using the 'Kahoot!' application can enhance students' vocabulary. Thus, it can be concluded that implementing game-based learning using the 'Kahoot!' application effectively improves students' vocabulary in Class X MPLB 3 at SMKN 1 Bone.